2021
DOI: 10.21203/rs.3.rs-151096/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Challenges and limits of Mechanical Stability in 3D Direct Laser Writing

Abstract: Direct laser writing is an effective technique for fabrication of complex polymeric 3D polymer networks using ultrashort laser pulses. Practically, it remains a challenge to design and fabricate high performance materials with different functions that possess a combination of high strength, substantial ductility, and tailored functionality, in particular for small feature sizes. To date, it is difficult to obtain a time-resolved microscopic picture of the printing process in operando. To close this gap, we her… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…The strong spatial confinement of the exposed region in two-photon polymerization (TPP) enables resolutions that cannot be achieved using traditional one-step one-photon absorption (1PA) processes 2,4,5 . Despite the tremendous progress in recent years 6 , 3D laser nanoprinting using TPP still faces different limitations [7][8][9][10] in resolution and speed that correlate strongly with the threshold laser power. This, in part, results from the limitations of the available photoinitiators (PIs) and resins: Kiefer et al 11 have recently reported a strong dependence of the printing sensitivity on the TPP initiation and, therefore, on the photochemical properties of the photoinitiator.…”
Section: Introductionmentioning
confidence: 99%
“…The strong spatial confinement of the exposed region in two-photon polymerization (TPP) enables resolutions that cannot be achieved using traditional one-step one-photon absorption (1PA) processes 2,4,5 . Despite the tremendous progress in recent years 6 , 3D laser nanoprinting using TPP still faces different limitations [7][8][9][10] in resolution and speed that correlate strongly with the threshold laser power. This, in part, results from the limitations of the available photoinitiators (PIs) and resins: Kiefer et al 11 have recently reported a strong dependence of the printing sensitivity on the TPP initiation and, therefore, on the photochemical properties of the photoinitiator.…”
Section: Introductionmentioning
confidence: 99%